Večrazsežnostni prikazi naravne in kulturne dediščine v projektu DEDI - Radovan, Dalibor (Knjižnica, 2012)
DEDI stands for the Digital Encyclopaedia of natural and Cultural Heritage in Slovenia which was a result of two prototype research and development projects DEDI and DEDI II in the period between 2008 and 2010. The two projects were co-financed by the Ministry of Higher Education, Science and Technology and the European Regional Development Fund in the frame of research and development projects e-content and e-services. DEDI is the first attempt of multimediarich digital representation of Slovenian natural and cultural heritage on a common web site offering verifiable, qualitative and complex content to a wide range of general public. Digital content (text, video records, audio records, photographs) is enriched by 2-dimensional and/or 3-dimensional visualisation of geographical data or even by 4-dimensional models with time component. 4D models combine 3D models with the time dimension. Thus it is possible to simulate the past, the current and the future condition of natural and cultural heritage objects, their changes, growth, deterioration or oscillation. 3D and 4D models are more explanatory, plastic and attractive to the unprofessional public thus increasingthe interest in the digital encyclopaedia. Technological solutions for the project were developed by the consortium partners in the field of web technologies who succeeded to locate all immovable natural and cultural heritage objects. The Google maps web platform is normally used for 2D representations but it is often too complex to represent a large amount of data. In order to meet the needs of the digital encyclopaedia data need to be structured and linked which is one of the main advantages of Geopedia, an interactive atlas which enables active user participation in adding and editing information on Slovenia. A 3D visualisation tool Gaea+ is used for real time visualisation of 3D models offering user-friendly presentation of any geospatial information and an interactive walk-through allowing users to move in 3D space. Many advanced DEDI files (dynamic multimedia representations or dediteka) of some natural and cultural objects of national importance were created. An advanced dediteka combines several object representation into interactive non-linear stories and upgrade them in various ways. The advanced dediteka "The story of Martin Krpan and his age" is a digitised story of Martin Krpan written in 1858 by Fran Levstik enriched by the audio record. The user can read a story and listen to the Slovenian language of the Levstik´s time.Two main digitisation criteria of equal importance were used for the selection of natural and cultural heritage objects: geographical area and the content value. The article describes a 4D simulation of the urban growth of Ljubljana and the virtual reconstruction of the Žiga Zois study room. 4D simulation of the growth of Ljubljana is based on historical and contemporary sources, i.e. 3D visualisation with time component. It is based on old city plans, digitised terrain model, national topographic maps, contemporary city plan and cadastre. 3D terrain models of buildings are enriched by a city plan of a specific period of time. The historical growth of the city is represented by a 2D dynamic map with floor plans and isochrones. 3D scanned exterior of the Žiga Zois Mansion is represented as well as a part of the interior with the virtual reconstruction of his study room where the collection of minerals was kept. Some specimens are 3D scanned. A few items of his literary opus are digitised, too.
Keywords: naravna dediščina; natural heritage; kulturna dediščina; cultural heritage; digital encyclopaedias; digitalne enciklopedije; digitization; digitalisation; digitalizacija; 3D modeli; 3D models; 4D modeli; 4D models; Slovenia; Slovenija